Impact of rising food prices on food security in Rajasthan and Gujarat - MAHAJAN, SUMIT; PAPANG, JANAILIN S; PANCHAL, INDU; B, SHARANAGOUDA (The Indian Journal of Agricultural Sciences, 2021)
A large area of Gujarat and Rajasthan is rain-fed exposing rural population to food prices spike due to frequent droughts. The present study was conducted in year 2020 and is based on NSSO data on household consumption expenditures of rural households of these states for the year 2009 to analyse the effects that food price changes have on food expenditure and calorie intake. The results show a strong negative effect of price rises on calorie intake. The negative impact of prices of foods particularly wheat, and milk is more on richer than on poorer households as they have the capability to cut calorie intake in the event of a price rise while its opposite for coarse cereals. The food prices particularly, milk, wheat and, pulses also have highly positive influence on food expenditure of poorer households. Rice price does not have much significant effect on food security in both the states.